Hydrology - The Science of Water - Muhammad Salik Javaid (IntechOpen, 2019)
The importance of the science of water, commonly called (3z(Bthe hydrologic science,(3y (Bis increasing day by day as water resources are depleting and becoming scarcer. These resources are either being polluted by human lifestyle, rendered unsuitable due to negligence and mismanagement, or their quantity is fast diminishing due to exhaustive extraction and consumption. With this state of affairs, in recent times, knowledge of the science of water has gained an impetus many times its original scale; and with that, its acquisition, expansion, research, advancement, and dissemination have become more important. With so many dimensions of hydrology available for exploration, research, and technological advancement, any contributory work will find its right place. This book will play its part in furthering the knowledge of the science of water and will prove useful reading for various cross-sections of academia, researchers, engineers, hydrologists, and all categories of water consumers.s
English
Keywords: Engineering; Physical Sciences; Engineering and Technology; Ecohydrology; Environmental Engineering